How to Stimulate Students’ Science Process Skill and Scientific Creativity in Physics Learning? - Haryanti, Septina Sri (Institut Agama Islam Negeri Padangsidimpuan, 2024)
Research has been carried out to stimulate students’ Science Process Skill (SPS) and Science Creativity (SC) in Physics learning on Polarization of Light through the development of problembased e-worksheet assisted with Fliphtml5. This research was a development research with the type of Design and Development Reaserch (DDR). The data from this research were in the form of validation results, assessment of students' science process skills and scientific creativity, as well as practicality test results were analyzed used mixed methods. The results of data validation show that the developed e- worksheet obtained a score of 95.5% with very high validity criteria. Assessment of students' science process skills and scientific creativity obtained a score of 87% in the highly stimulated criteria. Other results show that the practicality of the product is 89% in the very high category, the student response is 83% in the very good criteria, and the teacher's perception is 92% in the very possible criteria. Based on the results of data analysis, it can be concluded that the students’ science process skills and scientific creativity in Physics learning on Polarization of Light can be stimulated through problembased e-worksheet assisted with Fliphtml5.